As representações do comer saudável e suas traduções no cotidiano de mulheres que trabalham fora de casa - Duarte, Amélia Cristina Stival (2015)
This research was developed based on the argument that, however there a medical/ nutritional speech, the complex web of relationships involving the issue "food" makes it to be transferred to people's daily lives in a different way. Therefore the research followed with the aim to understand how women who work outside the home - a group of public servants that works in a public Health Institution in Goias - Brazil (Secretaria de Estado da Saúde de Goiás) - understand the sense of health food considering the multivocality of the subject. The methodology included conducting an observation-based ethnography and individual interviews with the servants that allowed to understand the representations of eating healthy structured into two main categories: space and time. In this sense, I came to the understanding that the meals eaten at home are linked to the notion of health for much more complex reasons than those involving nutritional matters. The house takes an idealized character, since most women are expanding their areas of expertise and thus acting more intensely out of the private sphere. So the healthy eating concept ends up being perceived more as a desire, a dream to be fulfilled, but given the constraints given by the demands of contemporary society ends up becoming a more guided practice in speech and with poor adherence in everyday life.